Effects on Consumer Welfare of Visitor Satisfaction with Recreation Information Availability: A Case Study of the Allegheny National Forest. (August 2015) - Cho, Seong-Hoon; Bowker, J.M.; Roberts, Roland K.; Kim, Seunggyu; Kim, Taeyoung; Lambert, Dayton M.
This research quantifies changes in consumer welfare due to changes in visitor satisfaction with the availability of information about recreational sites. The authors tested the hypothesis that an improvement in visitor satisfaction with recreation information increases the number of visits to national forests, resulting in increased consumer welfare. They tested the hypothesis with a travel cost model for the Allegheny National Forest using data from the National Visitor Use Monitoring (NVUM) programme. An ex ante simulation suggests that annual per capita consumer welfare increased when highly satisfactory recreation information was available. The findings, along with the expected costs of providing better recreation information, may be a useful reference for recreation site managers who wish to increase the number of visits in an economically effective way.